Role of malondialdehyde (MDA) in patients with breast cancer diseases - Eti Yerizel; Niki Astria; Daan Khambri (Acta Biochimica Indonesiana, 2019)
Background: Breast cancer is one of the most common cancers as well as one of the leading causes of cancer mortality in women worldwide. Cancer risk potentially continues to increase because of the many sources of exposure to carcinogenic chemical compounds. Carcinogenic compounds can contribute to free radical formation which might further interact and damage biomolecules such as lipids. Lipid peroxidation will increase malondialdehyde (MDA) levels, triggering gene mutations that leads to cancer. Objective: The purpose of this research was to measure and compare MDA levels between breast cancer patients and control. Methods: This research was observational research using a cross-sectional comparative design of 30 breast cancer patients and 30 healthy controls. The place of this research is in Ropanasuri specialized surgery hospital and biochemical laboratory, Faculty of Medicine, Andalas University, Padang. This research was conducted from August to September 2019. The MDA was measured using a spectrophotometer and an independent T-test was done. Results: The result of this research showed the mean MDA level of breast cancer patients was 3.98 ± 0.35 nmol/ml, higher than controls was 3.04 ± 0.36 nmol/ml with p-value = 0.001. Conclusion: There were significant differences in MDA levels among breast cancer patients and control in Ropanasuri specialized surgery hospital, Padang.